2011
DOI: 10.4161/auto.7.10.16490
|View full text |Cite
|
Sign up to set email alerts
|

Cleaving Beclin 1 to suppress autophagy in chemotherapy-induced apoptosis

Abstract: RW, et al. Following cytochrome c release, autophagy is inhibited during chemotherapy-induced apoptosis by caspase 8-mediated cleavage of Beclin 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 1 publication
1
26
0
Order By: Relevance
“…Studies have indicated that cleaved beclin-1 fails to induce autophagy but can associate with mitochondria to induce apoptosis. 68,69 In conclusion, the correlation between ineffective bacterial Figure 7 IFNAR1 signaling increased the numbers of IL-10eproducing-CD3 þ CD4 þ CD25 þ T cells and the number of FOXP3-expressing Tregs in liver during fatal ehrlichial infection. A: Flow cytometry analysis of the percentage of CD3 þ CD4 þ CD25 þ and IL-10 þ CD3 þ CD4 þ CD25 þ T cells in spleen at day 7 p.i.…”
Section: Ehrlichiae Block Autophagy Processing That Is Dependent On Imentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have indicated that cleaved beclin-1 fails to induce autophagy but can associate with mitochondria to induce apoptosis. 68,69 In conclusion, the correlation between ineffective bacterial Figure 7 IFNAR1 signaling increased the numbers of IL-10eproducing-CD3 þ CD4 þ CD25 þ T cells and the number of FOXP3-expressing Tregs in liver during fatal ehrlichial infection. A: Flow cytometry analysis of the percentage of CD3 þ CD4 þ CD25 þ and IL-10 þ CD3 þ CD4 þ CD25 þ T cells in spleen at day 7 p.i.…”
Section: Ehrlichiae Block Autophagy Processing That Is Dependent On Imentioning
confidence: 96%
“…Beclin-1 is an important protein that mediates autophagy initiation and nucleation, and its function is thought to be controlled by cleavage. 58,68 The WT mice and all knockout mice expressed similar levels of fulllength beclin-1 in the liver tissues on day 7 p.i. (Figure 11, A and C).…”
Section: Ehrlichiae Block Autophagy Processing That Is Dependent On Imentioning
confidence: 99%
“…A number of groups have observed caspase induced site specific cleavage of Beclin 1 following induction of apoptosis [27,28]. These results led to a hypothesis that Beclin 1cleavage may inhibit protective autophagy in cells committed to cell death.…”
Section: Regulation Of Apoptosis By Autophagy Proteinsmentioning
confidence: 99%
“…Validation of the involvement of casp8 in autophagy came from studies showing that casp8 mediated the cleavage and subsequent inactivation of ATG3 and beclin 1 [43,44]. During TNF-related apoptosis-inducing ligand (TRAIL)-induced autophagy, the large catalytic subunit of casp8 was found to be degraded by the autophagosome [44,45]. These results suggest crosstalk between apoptosis and autophagy (Figure 1-2).…”
Section: Caspase-8mentioning
confidence: 97%
“…Yu et al further showed that the inhibition of casp8 was critical in order to induce autophagy mediated by ATG3 (autophagy-related gene 7) and beclin-1 [42]. Validation of the involvement of casp8 in autophagy came from studies showing that casp8 mediated the cleavage and subsequent inactivation of ATG3 and beclin 1 [43,44]. During TNF-related apoptosis-inducing ligand (TRAIL)-induced autophagy, the large catalytic subunit of casp8 was found to be degraded by the autophagosome [44,45].…”
Section: Caspase-8mentioning
confidence: 99%